The Effect Of Guided Reading Method Through The Use Of Flash Cards On Students ' Reading Ability And Self-Confidence - Sukesih, Avi; Houtman, Houtman; Izzati, Arini Noor (Elementary Teacher Education Program, Majalengka University, 2024)
Reading ability is a fundamental skill crucial for the academic and social development of students, particularly for third-grade elementary students who are at the initial stage of advanced literacy. This study aims to evaluate the impact of a guided reading method combined with the use of flashcards on students' reading abilities and self-confidence. An experimental method was employed, utilizing a pre-experimental one-group pretest-posttest design. The sample was selected through purposive sampling, comprising a total of 28 students from State Elementary School 27 Rabadompu Timur. The research findings indicate that the average pretest score was approximately 61.29, while the posttest average score increased to around 74.54, demonstrating the effectiveness of the flashcard method in enhancing students' reading abilities. The paired samples test revealed a significance value (p-value) of 0.000, which is well below the significance level of 0.05, affirming that the use of flashcards significantly improves students' reading skills. Additionally, self-confidence responses indicated that students felt more confident during reading activities, and participatory observation results suggested that the use of flashcards enhanced overall student engagement and enthusiasm. As a visual aid, flashcards facilitated information retention and created a more interactive learning environment. Future research may explore the effectiveness of flashcards tailored to varying levels of complexity.